Analisis Kualitas Aplikasi Grabag Guide Menggunakan Standar ISO/IEC 25010 - Yusuf Wahyu Setiya Putra; Sukris Sutiyatno; Tri Yusnanto; Gatot Susilo; Muhammad Rafidan Birul Arzaq (Infotekmesin, 2024)
The Grabag Guide application was created in 2023 and is used by more than 200 users and there are problems in terms of user ease in accessing information in the application. The aim of this research is to analyze the quality of the Grabag Guide Android application using the ISO/IEC 25010 standard and provide recommendations for improving the quality of the application. The method used is a quantitative method where data from respondents is used as many as 42 users. The questionnaire results were analyzed using the Structural Equation Modeling (SEM) model. The result is that of the seven hypotheses proposed, six hypotheses have a positive and significant effect on application performance. Functional outcome scores (CR 1.980), compatibility (CR 1.825), ease of use (CR 2.225), reliability (CR 4.150), security (CR 3.789), maintainability (CR 2.631), and portability (CR 2.067). In conclusion, the important feature is compatibility, so this feature can be prioritized when evaluating the quality of the Grabag Guide application. The results of this research can be used as parameters for creating quality tourism applications in other sub-districts in Magelang Regency.